Downregulation of the lycopene ϵ‐cyclase gene increases carotenoid synthesis via the β‐branch‐specific pathway and enhances salt‐stress tolerance in sweetpotato transgenic calli. Issue 4 (1st October 2012) - Kim, Sun Ha; Kim, Yun‐Hee; Ahn, Young Ock; Ahn, Mi‐Jeong; Jeong, Jae Cheol; Lee, Haeng‐Soon; Kwak, Sang‐Soo
Abstract Lycopene ϵ‐cyclase (LCY‐ϵ) is involved in the first step of the α‐branch synthesis pathway of carotenoids from lycopene in plants. In this study, to enhance carotenoid synthesis via the β‐branch‐specific pathway [which yields β‐carotene and abscisic acid (ABA)] in sweetpotato, the expression of IbLCY‐ϵ was downregulated by RNAi (RNA interference) technology. The RNAi‐IbLCY‐ϵ vector was constructed using a partial cDNA of sweetpotato LCY‐ϵ isolated from the storage root and introduced into cultured sweetpotato cells by Agrobacterium‐mediated transformation. Both semi‐quantitative Reverse transcription polymerase chain reaction (RT‐PCR) of carotenoid biosynthesis genes and high‐performance liquid chromatography (HPLC) analysis of the metabolites in transgenic calli, in which the LCY‐ϵ gene was silenced, showed the activation of β‐branch carotenoids and its related genes. In the transgenic calli, the β‐carotene content was approximately 21‐fold higher than in control calli, whereas the lutein content of the transgenic calli was reduced to levels undetectable by HPLC. Similarly, expression of the RNAi‐IbLCY‐ϵ transgene resulted in a twofold increase in ABA content compared to control calli. The transgenic calli showed significant tolerance of 200 mM NaCl. Furthermore, both the β‐branch carotenoids content and the expression levels of various branch‐specific genes were higher under salt stress than in control calli. These results suggest that, in sweetpotato, downregulation of the ϵ‐cyclization of lycopene increases carotenoid synthesis via the β‐branch‐specific pathway and may positively regulate cellular defenses against salt‐mediated oxidative stress.